Avaliação do papel de genes da via de indução de espécies reativas de oxigènio (ROS) na ativação do inflamassoma frente a infecção por toxoplasma gondii e neospora caninum - Torres, Jhoan David Aguillon (2020)
Parasitic infections of the phylum apicomplexa are widely studied as they cause clinical and economic problems. Toxoplasma gondii represents a public health problem because it affects immunodeficient individuals and intrauterine infected fetuses or neonates; Neospora caninum, on the other hand, causes great economic losses in the agriculture sector because it is the main cause of bovine abortions. Several studies have shown that there are great differences between T. gondii and N. caninum, such as the type of intermediate and definitive hosts and pathogenesis. It is also known that these parasites use similar mechanisms for infection and therefore share some similarities in the immune response that induces, for example, the induction of a Th1 type response to control parasitic replication. Additionally, the inflammasome - a protein complex that triggers the maturation of IL-1β and IL-18 and leads the cells to pyroptosis - has been extensively studied in recent years as a parasitic control mechanism, as well as its relationship with other cellular mechanisms of parasitic control such as the production of reactive oxygen species (ROS). It is known that infection by parasites belonging to the phylum apicomplexa is capable of inducing ROS production and inflammation activation. In this sense, the aim of the present study was to correlate relevant genes in the induction of reactive oxygen species with inflammation activation during murine macrophage infection with T. gondii and N. caninum. Through the analysis of RNAseq of macrophages infected with both parasites and the expression later validated by real-time PCR, it was found that the infections by both parasites can regulate the expression of genes associated with the ROS pathway. Based on this information, using the CRISPR/Cas9 genomic editing technology, genetically deficient macrophages were generated from central components of this signaling pathway to evaluate their roles in the induction and activation of critical components of the inflammasome complex. Based on these cells, we observed that NOX1 and NOX2 are closely related to the activation of Caspase-1/11 by infections, while NOX1 and MPO are essential for the expression of ASC in the analyzed cells. Additionally, parasite-specific differences were found in the genes analyzed. Thus, these findings show that genes related to the ROS induction pathway actively participate in the formation of the inflammasome complex during infections by T. gondii and N. caninum protozoans.